2002
DOI: 10.1073/pnas.082093299
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of retinoic acid production and growth by ubiquitously expressed alcohol dehydrogenase Adh3

Abstract: Influence of vitamin A (retinol) on growth depends on its sequential oxidation to retinal and then to retinoic acid (RA), producing a ligand for RA receptors essential in development of specific tissues. Genetic studies have revealed that aldehyde dehydrogenases function as tissue-specific catalysts for oxidation of retinal to RA. However, enzymes catalyzing the first step of RA synthesis, oxidation of retinol to retinal, remain unclear because none of the present candidate enzymes have expression patterns tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
125
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 52 publications
(80 reference statements)
5
125
1
4
Order By: Relevance
“…In particular, acetaldehyde is the oxidation product of ethanol and is involved in the liver damage observed in individuals chronically exposed to alcohol (35,36). Butyraldehyde is a catabolite of butyryl-CoA (www.expasy.org/cgi-bin/search-biochem-index), and retinaldehyde is the direct precursor of the vitamin A active metabolite retinoic acid (37,38). As shown in Table IV, upon incubation with purified AOH1 and AOX1, benzaldehyde and retinaldehyde are rapidly oxidized and reduce the electron acceptor potassium ferricyanide.…”
Section: The Structure Of the Promoter Region Of The Aoh1 Gene In Dbamentioning
confidence: 99%
“…In particular, acetaldehyde is the oxidation product of ethanol and is involved in the liver damage observed in individuals chronically exposed to alcohol (35,36). Butyraldehyde is a catabolite of butyryl-CoA (www.expasy.org/cgi-bin/search-biochem-index), and retinaldehyde is the direct precursor of the vitamin A active metabolite retinoic acid (37,38). As shown in Table IV, upon incubation with purified AOH1 and AOX1, benzaldehyde and retinaldehyde are rapidly oxidized and reduce the electron acceptor potassium ferricyanide.…”
Section: The Structure Of the Promoter Region Of The Aoh1 Gene In Dbamentioning
confidence: 99%
“…Biochemical studies indicate that both isomers of RA can be generated in vitro from vitamin A (retinol) by cytosolic alcohol dehydrogenases (21) and microsomal short-chain dehydrogenases (22,23), which each catalyze oxidation of all-trans-retinol and 9-cis-retinol to the corresponding retinaldehyde derivatives, followed by cytosolic retinaldehyde dehydrogenase (Raldh), which catalyzes further oxidation of both all-trans-retinaldehyde and 9-cis-retinaldehyde to produce all-trans-RA or 9-cis-RA (24,25). Mouse genetic studies support a role in RA synthesis for alcohol dehydrogenase genes Adh1, Adh3, and Adh4 (26,27) as well as Raldh genes Raldh2 (Aldh1a2) (28,29) and Raldh1 (Aldh1a1) (30). Thus, 9-cis-RA can potentially be synthesized by presently known enzymes, or it can be derived from isomerization of all-trans-RA (8).…”
mentioning
confidence: 99%
“…Genetic studies in mice have demonstrated that oxidation of retinol to retinaldehyde is ubiquitous during development as it is controlled by ubiquitously expressed alcohol dehydrogenase Adh3 and several additional overlapping tissue-specific enzymes (21). As for the second step, mouse genetic studies have shown that oxidation of retinaldehyde to RA is controlled by tissue-specific retinaldehyde dehydrogenase genes including Raldh1 (Aldh1a1) (22), Raldh2 (Aldh1a2) (19,23), and Raldh3 (Aldh1a3) (24).…”
mentioning
confidence: 99%